Impact of thermal and biotechnological processing on the bioaccessibility and allergenic peptide profile of white lupin (Lupinus albus) - Ozyurek-Arpa, Fatmanur; Yaman, Mustafa; Çakır, Bilal; Kalkan, Indrani (Frontiers in Nutrition, 2026)
BackgroundWhite lupin (Lupinus albus) is increasingly recognized as a sustainable, highprotein functional food ingredient, yet its potential allergenicity remains a significant concern for food safety. This study aimed to investigate the impact of thermal and biotechnological processing methods on the bioaccessibility and allergenic peptide profiles of white lupin seeds.MethodsLocal lupin seeds were subjected to four distinct processing techniques: boiling, microwave cooking, fermentation, and enzymatic treatment. To evaluate protein stability and allergen release under physiological conditions, the processed samples underwent simulated in vitro gastrointestinal digestion as well as standard protease hydrolysis. The resulting peptide sequences were characterized using liquid chromatography with tandem mass spectrometry (LC-MS/MS) and analyzed via in silico bioinformatics tools to predict potential allergenicity.ResultsThe results indicated that biotechnological processes, specifically enzymatic treatment and fermentation, generated a higher diversity of detectable peptides and distinct allergenic matches following digestion compared to thermal treatments alone. Furthermore, samples subjected to the simulated gastrointestinal digestion model revealed a broader spectrum of conserved epitope matches in allergen databases compared to standard hydrolysis, suggesting that this model provides a more accurate representation of the allergenic peptides likely to persist in the human digestive tract.DiscussionThese findings demonstrate that processing methods significantly modulate the structural integrity and predicted allergenic profile of lupin proteins, providing a molecular basis for selecting appropriate processing strategies in the development of safer lupin-based functional foods.